1996
DOI: 10.1021/om9603070
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Solid-State Structure, Solution Dynamics, and Reactivity of the Trinuclear Open Cluster Anion [Re2(CO)9{(μ-H)ReH(CO)4}]-

Abstract: The addition of [M(CO) 5 ] -anions (M ) Re, Mn) to the electronically unsaturated [Re 2 (µ-H) 2 (CO) 8 ] complex rapidly and selectively gives the trinuclear anions [ReM(CO) 9 {(µ-H)ReH-(CO) 4 }] -(M ) Re, 2; M ) Mn, 3). The single-crystal X-ray analysis of [NEt 4 ]2 has revealed a fully staggered L-shaped structure. The anion 2 has been obtained with good selectivity also by reacting (i) [Re 2 (CO) 9 (THF)] with [H 2 Re(CO) 4 ] -and (ii) [HRe 2 (CO) 9 ] -with [HRe-(CO) 5 ]. The last reaction can be reversed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
(60 reference statements)
3
23
0
2
Order By: Relevance
“…In addition, spacers (for example, polyphenyls, [6] alkenes, [7] or alkynes [5,8] ) can also be selected to serve as electron-conducting active components to promote long-range electronic coupling between terminal subunits or (for example, saturated hydrocarbons [9] ) to serve as passive connecting components. Systems with unsaturated sp carbon chains (C n ) between two subunits constitute one of the most fundamental classes of one-dimensional molecular wires, however, intense studies in numerous laboratories have focused on the systems with alkynes or acetylenyl bridges.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, spacers (for example, polyphenyls, [6] alkenes, [7] or alkynes [5,8] ) can also be selected to serve as electron-conducting active components to promote long-range electronic coupling between terminal subunits or (for example, saturated hydrocarbons [9] ) to serve as passive connecting components. Systems with unsaturated sp carbon chains (C n ) between two subunits constitute one of the most fundamental classes of one-dimensional molecular wires, however, intense studies in numerous laboratories have focused on the systems with alkynes or acetylenyl bridges.…”
Section: Methodsmentioning
confidence: 99%
“…tetranuclear clusters, [6,7] by allowing hydrido ± carbonyl rhenates to react with [Re 2 (CO) 9 L], where L is a very labile ligand such as THF or H 2 O (the otherwise labile MeCN ligand is not labile enough to be substituted by neutral [8] or anionic [6] hydride complexes). Recently the di-substituted complex 1,2-eq,eq-[Re 2 (CO) 8 8 ] with diazomethane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…shown that replacement of X À with isolobal carbonylmetalates affords trinuclear L-shaped cluster anions, [19,33] due to the formation of MÀRe bonds (Scheme 8). More recently we proved that also carbonylates containing terminal hydrido ligands can add to 1, [22,18] through M-H-Re interactions (Scheme 8).…”
Section: The Unsaturated [Re 2 (M-h) 2 (Co) 8 ] Complex and Its Reactmentioning
confidence: 99%
“…[18,19] On the other hand, ring opening by the addition of electron donors [20] is penalized by the fact that the number of ring clusters of nuclearity higher than 3 is very limited.…”
Section: Introductionmentioning
confidence: 99%